Promoting retention, enabling success: Discovering the potential of student support circles. (September 2016) - Bass, Janice; Walters, Caroline; Toohill, Jocelyn; Sidebotham, Mary
Abstract: Retention of students is critical to education programs and future workforce. A mixed methods study evaluated student engagement within a Bachelor of Midwifery program and connection with career choice through participation in student support circles. Centred on the Five Senses of Success Framework (sense of capability, purpose, identity, resourcefulness and connectedness) and including four stages of engagement (creating space, preparing self, sharing stories, focused conversations), the circles support and develop student and professional identity. Of 80 students 43 (54%) provided responses to a two item survey assessed against a five point Likert scale to determine utility. Using a nominal group technique, student's voices gave rich insight into the personal and professional growth that participation in the student support circles provided. Evaluated as helpful to first year students in orientating to university study and early socialisation into the profession, the circles appear to influence the development of a strong sense of professional identity and personal midwifery philosophy based on the relational nature of the midwife being with woman rather than doing midwifery. This suggests that student support circles positively influence perceptions and expectations, contributing to a shared sense of purpose and discipline connection, for enhancing student retention and future workforce participation. Highlights: Student Support Circles (SSC) are effective in supporting students transitioning to university. SSC developed five senses for student success: sense of capability, purpose, identity, resourcefulness and connectedness. Nominal group technique evaluation provided a student centred approach to generating data. Peer and academic support strategies within SSC programs are valuable mechanisms for socialising students to online components of curricula. The embedding of self-awareness, self-efficacy and reflexivity within the SSC process may build resilience in students.